ART DRAWING THERAPY UNTUK MENGURANGI TINGKAT DEPRESI PADA IBU POST PARTUM BLUES - Martina Ekacahyaningtyas; Yunita Wulandari; Nur Fitria Rahmah Ramdaniati (LPPM STIKES KENDAL, 2020)
Post Partum Blues is a regular expression of sorrow or gloom which temporary appears for two days to two weeks following a childbirth. In such a condition, a post partum mother experiences feeling of sadness, fear, sleep disruption, concentration disorder and tension or anxiety. This research aims to determine effect of art drawing therapy on depression level of post partum blues mother.This research used the quasi experimental research method with pre test and post test nonequivalent control group design. It was conducted in the working area of community health center of Sibela Surakarta. The population in this study were post partum blues mothers in the working area of ​​Puskesmas Sibela. Non probability sampling with purposive sampling was used to determine its samples. They consisted of 36 post partum blues mother, and they were divided into two groups: 18 in the treatment group and 18 in the control group. The instrument for measuring maternal depression in the post partum blues was the Edinburgh Postnatal Depression Scale (EPDS) questionnaire.The data of the research were analyzed by using the wilcoxon’s test and the mann whitney’s test. The result of the wilcoxon’s test shows that decrease level of depression between the pre test and post test in the treatment group by the p value 0,000 and that of the mann whitney’s test shows that there was a difference of depression level between the treatment group and the control group by the p value 0,036. The administration of art drawing therapy had an effect on the level of depression of the post partum blues mother in the working area of community health center of Sibela Surakarta. Art Drawing Therapy can be used as one of the interventions for post partum blues mother treatment.